Knowledge, Attitude and Practice of Youth in Panchayats, Kerala - K Gireesan (KILA Journal of Local Governance, 2013)
Active involvement of youth can provide a strong support for the Local Governments. Importance of an enabling environment, wherein both the local Governments and the youth come together and function as ‘partners in development’, needs no emphasis. In this context, the research study of Knowledge, Attitude and Practice of Youth in Panchayati Raj was taken up by RGNIYD. As part of the study, 75 young elected members and 225 young citizens were contacted from 24 Grama Panchayats, who were drawn from four Blocks of Thrissur district of Kerala. As a summary of the study, this paper brings out valuable insights towards mainstreaming the issues of youth so as to enable more and more active and constructive minded youth to bring good governance to the grassroot level.